The Application of Deep Learning in Enhancing the Effectiveness of Islamic Religious Education Curriculum in Madrasahs - Idham Idham; Rokimin Rokimin; Muhamad Towil Akhirudin; Miftah Hur Rahman Zh; Zahid Zufar At Thaariq (Management of Education: Jurnal Manajemen Pendidikan Islam, 2026)
This study aims to investigate the application of deep learning technologies in enhancing the effectiveness of the Islamic Religious Education (IRE) curriculum in madrasahs. Employing a Systematic Literature Review (SLR) methodology based on the PRISMA 2020 guidelines, this research synthesizes findings from 42 peer-reviewed articles published between 2020 and 2025, sourced from Scopus-indexed journals and SINTA-accredited national journals. The review identifies five major thematic areas: (1) adaptive and personalized learning through deep learning algorithms, (2) automated curriculum content analysis using Natural Language Processing, (3) predictive analytics for student learning outcomes, (4) intelligent assessment and feedback systems, and (5) deep learning-enhanced multimedia for IRE instruction. Findings reveal that deep learning applications hold significant promise for personalizing IRE content delivery, improving student engagement with Quranic and Hadith-based materials, and enabling data-driven curriculum evaluation. However, substantial challenges persist, including limited technological infrastructure in madrasahs, insufficient teacher digital literacy, ethical considerations surrounding AI in religious education, and the scarcity of Arabic and Indonesian language training datasets for deep learning models. This study contributes to the literature by bridging the gap between artificial intelligence research and Islamic education, proposing a conceptual framework for the systematic integration of deep learning into the IRE curriculum. The findings provide actionable recommendations for policymakers, madrasah administrators, and educational technology developers seeking to modernize Islamic education while preserving its spiritual and moral foundations.